2019
DOI: 10.1177/0739456x19827083
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Some Articles in Planning Journals Get Cited More than Others?

Abstract: The planning literature has taken a recent interest in journal article citation counts, which are often used to measure the scholarly impact of articles, authors, or university departments. However, little is known about the factors that determine citation counts for planning-related articles. We find that citation counts in planning vary across planning topics and are also influenced by other journal, author, and article-related factors. We provide recommendations to planning researchers for increasing the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 126 publications
(215 reference statements)
2
13
1
1
Order By: Relevance
“…However, specialist journals can be highly cited, doing well in various quantitative metrics, particularly in some subfields. In planning, transportation and theory papers tend to do well in terms of citations, whereas those in environment and diversity do far less well (Stevens, Park, Tian, Kim, & Ewing, 2019). This echoes more general patterns across disciplines and specialist journals, with huge differences in citation rates and impact factors even in the sciences (Hicks, Wouters, Waltman, de Rijcke, & Rafols, 2015).…”
Section: Assessing Generalist Journalsmentioning
confidence: 98%
“…However, specialist journals can be highly cited, doing well in various quantitative metrics, particularly in some subfields. In planning, transportation and theory papers tend to do well in terms of citations, whereas those in environment and diversity do far less well (Stevens, Park, Tian, Kim, & Ewing, 2019). This echoes more general patterns across disciplines and specialist journals, with huge differences in citation rates and impact factors even in the sciences (Hicks, Wouters, Waltman, de Rijcke, & Rafols, 2015).…”
Section: Assessing Generalist Journalsmentioning
confidence: 98%
“…To date there are few bibliometric analyses specifically on urban planning scholarship. Examples of such analyses for urban planning academics include Stiftel, Rukmana, and Alam (2004), followed several years later by Sanchez (2017), Pojani, Olvera-Garcia, Sipe, and Byrne (2018), Stevens, Park, Tian, Kim, and Ewing (2019), and Sanchez (2020). The bibliometric literature has long recognized the differential rates of citation by topics, following the assumption that certain sub-fields are more popular, have more publications and therefore greater chances of citation (see Bornmann, Schier, Marx, & Daniel, 2012).…”
Section: Scholarly Citationsmentioning
confidence: 99%
“…The bibliometric literature has long recognized the differential rates of citation by topics, following the assumption that certain sub-fields are more popular, have more publications and therefore greater chances of citation (see Bornmann, Schier, Marx, & Daniel, 2012). In their analysis of factors effecting urban planning citations, Stevens et al (2019) included variables indicating whether the publication topic was related to one of 13 selected subtopics. They found that compared to 'transportation,' nearly all other sub-fields were cited less frequently, with many of the regression coefficients being insignificant.…”
Section: Scholarly Citationsmentioning
confidence: 99%
“…These form urban planning subfields that are reflected in the types of publication topics, as well as the breadth of journals where these publications appear. Of the few journal articles about urban planning citation activity beginning with Stiftel, Rukmana, and Alam [31] (followed several years later by Sanchez [32], Pojani et al [33] and Stevens et al [34]), only Stevens et al have explicitly tried to measure topical differences within urban planning citation patterns. In their analysis of factors affecting urban planning citations, they examined whether the publication topics were related to thirteen selected topics.…”
Section: Citation Analysesmentioning
confidence: 99%